The Effectiveness of Decentralization Policy in Local Government Administration - Zaenal Arifin Hoesein; Arifudin Arifudin; Susi Dian Rahayu (Jurnal Akta, 2022)
Article 18 paragraph (2) and paragraph (5) of the 1945 Constitution stipulates that the Regional Government is authorized to regulate and manage its own government affairs according to the principles of autonomy and co-administration and is granted the widest possible autonomy. The granting of the widest possible autonomy to regions is directed at accelerating the realization of community welfare through service improvement, empowerment, and community participation. Regional formation is basically intended to improve public services in order to accelerate the realization of community welfare as well as as a means of political education at the local level. For this reason, the formation of a region must take into account various factors such as economic capacity, regional potential, area, population, and considerations from socio-political, socio-cultural, defense and security aspects, as well as other considerations and conditions that enable the region to organize and realize the objectives of the establishment. By using descriptive analytical research method the results of this research are decentralization is the delegation of government power from the central government to regions to manage their own households, or regions are given autonomy to become autonomous regions. Decentralization is intended to give authority from the state government to local governments to regulate and manage certain affairs as their own household affairs. Therefore, the birth of Act No. 23 of 2014 concerning Regional Government, especially the essence of decentralization, is basically in the framework of accelerating the distribution of community welfare, especially in the regions.